Development of a Competitive Time‐Resolved Fluoroimmunoassay for Paclitaxel. Issue 3 (20th December 2017) - Cui, Qian; Tanaka, Hiroyuki; Shoyama, Yukihiro; Ye, Hao‐Ting; Li, Fang; Tian, En‐Wei; Wu, Ying‐Song; Chao, Zhi
Abstract: Introduction: Paclitaxel (Tax) is a diterpene alkaloid isolated from Taxus species and has proved clinically effective in treating a number of malignancies. Current quantitative analytical methods for Tax such as high‐performance liquid chromatography (HPLC) often involve complicated sample preparation procedures with low recovery rates. Objective: To establish a rapid and sensitive time‐resolved fluoroimmunoassay (TRFIA) for measuring Tax in Taxus materials with convenient sample preparation and a high recovery rate. Methods: Rabbit anti‐mouse IgG was coated onto a 96‐well microplate, which was then incubated with standard solutions of Tax and anti‐Tax monoclonal antibody 3A3. A Eu 3+ ‐labelled conjugate of Tax and human serum albumin was used as the tracer. The luminescent system was enhanced with a solution containing 2‐naphthoyltrifluoroacetone. Results: The established TRFIA showed a linear response within the Tax concentration range of 3.2 to 80 ng/mL, with a limit of detection of 1.4 ng/mL. The intra‐ and inter‐assay coefficient of variation of the assay was 9.6% and 9.7%, respectively, with an average recovery rate from spiked samples of 108.5%. Tax contents in Taxus samples were determined using both the established TRFIA system and a previously established enzyme‐linked immunosorbent (ELISA), and the results of two assays were well correlated. Conclusion: This TRFIA system shows a high sensitivity, precision and accuracy for detection of Tax. This assay, which is convenient and less time‐consuming, allows rapid analysis of Tax and provides another option for Tax measurement for quality control of Taxus materials and products. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A competitive time‐resolved fluoroimmunoassay (TRFIA) for measuring paclitaxel using anti‐paclitaxel monoclonal antibody was set up. The established TRFIA provided a linear response from 3.2 to 80 ng/mL, and a limit of detection at 1.4 ng/mL, which was three times more sensitive than the conventional enzyme‐linked immunosorbent assay (ELISA), and was time‐saving for at least 1 h. The assay may provide another option for the paclitaxel measurement in the quality control of Taxus materials and products.